Tumor downstaging as an intermediate endpoint to assess the activity of neoadjuvant systemic therapy in patients with muscle‐invasive bladder cancer. Issue 18 (31st May 2019) - Martini, Alberto; Jia, Rachel; Ferket, Bart S.; Waingankar, Nikhil; Plimack, Elizabeth R.; Crabb, Simon J.; Harshman, Lauren C.; Yu, Evan Y.; Powles, Thomas; Rosenberg, Jonathan E.; Pal, Sumanta K.; Vaishampayan, Ulka N.; et al.
Abstract : Background: Achieving a pathologic complete response (pCR) with neoadjuvant chemotherapy (NAC) in patients with muscle‐invasive bladder cancer (MIBC) has been associated with improved overall survival (OS). This study was aimed at evaluating the impact of pathologic downstaging (pDS; ie, a pT stage at least 1 stage lower than the pre‐NAC cT stage) on the OS of patients with MIBC treated with NAC. Methods: The Retrospective International Study of Cancers of the Urothelial Tract (RISC) and the National Cancer Database (NCDB) were queried for cT2‐4N0M0 patients treated with NAC. A multivariable Cox model including either pDS or pCR was generated. A nested model was built to evaluate the added value of pDS (excluding patients achieving a pCR) to a model including pCR alone. C indices were computed to assess discrimination. NCDB was used for validation. The treatment effect of NAC versus cystectomy alone in achieving pDS was estimated through an inverse probability–weighted regression adjustment. Results: Overall, 189 and 2010 patients from the RISC and NCDB cohorts, respectively, were included; pDS and pCR were achieved by 33% and 35% and by 20% and 15% in RISC and NCDB, respectively. In both data sets, pDS and pCR were associated with better OS and C indices. Adding pDS excluding pCR to the model with pCR fit the data better (likelihood ratio, P  = .019 for RISC and P  < .001 for NCDB), and it yielded better discrimination (incremental C index, 4.2 for RISC and 1.6 for NCDB). The treatment effect of NAC in achieving pDS was 2.07‐fold ( P  < .001) in comparison with cystectomy alone. Conclusions: A decrease of at least 1 stage from the cT stage to the pT stage is associated with improved OS in patients with MIBC treated with NAC. Abstract : Using 2 different cohorts, this study demonstrates that a decrease in tumor size, even without complete disappearance, is associated with better survival than no response in patients with muscle‐invasive bladder cancer treated with neoadjuvant chemotherapy.